Structural, electrical and magnetic properties of Sr1-xBixTiO3-δ ceramics. (2nd January 2020) - El-Sayed, S.; Hassen, A.
ABSTRACT: The structural, electrical and magnetic properties of Sr1- x Bi x TiO3-δ, ( x  = 0.10, 0.20, and 0.30) ceramics have been investigated. The X-ray powder diffraction (XRD) patterns at room temperature indicate that the structure of the samples is cubic with Pm3 m space symmetry group. The conduction of all investigated samples follows the three-dimensional variable-range hopping (VRH) model within the temperature range 100 K ≤  T  ≤ 300 K. It was noticed that the paramagnetic behaviour depends on the content of Bi ions. The effective paramagnetic magnetic moment increased as the Bi content increased.